2021
DOI: 10.1002/mp.15376
|View full text |Cite
|
Sign up to set email alerts
|

A CT‐less approach to quantitative PET imaging using the LSO intrinsic radiation for long‐axial FOV PET scanners

Abstract: Long-axial field-of -view (FOV) positron emission tomography (PET) scanners have gained a lot of interest in the recent years.Such scanners provide increased sensitivity and enable unique imaging opportunities that were not previously feasible. Benefiting from the high sensitivity of a long-axial FOV PET scanner,we studied a computed tomography (CT)-less reconstruction algorithm for the Siemens Biograph Vision Quadra with an axial FOV of 106 cm. Methods: In this work, the background radiation from radioisotope… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 51 publications
0
20
0
1
Order By: Relevance
“…While, in this study, MLAA-TX has shown no significant advantage over MLTR-based AC, it has to be noted that, at higher-count PET scans, the PET data can contribute more to estimation of the μ-map, as shown in the previous studies ( 34 , 40 ). However, as depicted in Figure 11 , the TOF-MLAA algorithm may require more iterations to converge to a solution that does not suffer from transmission-emission crosstalk artifacts.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…While, in this study, MLAA-TX has shown no significant advantage over MLTR-based AC, it has to be noted that, at higher-count PET scans, the PET data can contribute more to estimation of the μ-map, as shown in the previous studies ( 34 , 40 ). However, as depicted in Figure 11 , the TOF-MLAA algorithm may require more iterations to converge to a solution that does not suffer from transmission-emission crosstalk artifacts.…”
Section: Discussionmentioning
confidence: 51%
“…To mitigate the effect of Compton scattering on quantification accuracy of the μ-maps and activity maps consequently, the MLTR-reconstructed μ-maps that included Compton-scattered events were scaled with a global scaling factor similar to the approach proposed by ( 40 ). This was done by finding the water peak in the histogram of the image voxel values of the μ-maps and computing a global scaling factor to shift the histogram peak to the attenuation coefficient of water.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These µ-maps were mapped to 511 keV, and then averaged and smoothed using a Gaussian filter with a full width half maximum (FWHM) of 4 mm. The resulting LSO-TX derived µ-map and the TOF emission sinogram were used as inputs to MLACF algorithm to jointly reconstruct a PET image and an MLACF-derived attenuation map using 20 global iterations [ 30 ]. Two sets of MLACF-derived attenuation maps were generated by using the LSO-TX data acquired pre- and post- 18 F-FDG injection, referred as µ-map MLACF-PRE and µ-map MLACF-POST in the rest of the paper respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The radioisotope lutetium-176 ( 176 Lu) found in LSO scintillators of PET detectors decays with a half-life of 38 billion years, emitting gamma rays with 307, 202, and 88 keV during the process [ 29 ]. We have previously demonstrated that this LSO background radiation can be detected using a high sensitivity LAFOV PET scanner and developed a method to generate µ-maps using MLACF algorithm with LSO transmission (LSO-TX) data (µ-map MLACF ) [ 30 ]. In this paper, we extend the previous method by incorporating a deep learning-based model to synthesize enhanced whole-body µ-maps (µ-map DL-MLACF ) based on µ-map MLACF images.…”
Section: Introductionmentioning
confidence: 99%